Porous nanocrystalline TiO2 with high lithium-ion insertion performance - Wang, J.; Zhou, Y.; Hu, Y.; O'Hayre, R.; Shao, Zongping (2013)
Porous nanocrystalline anatase TiO2 was prepared by a modified hydrolytic route coupled with an intermediary amorphization/recrystallization process. The phase structure and morphology of the products were analyzed by X-ray diffraction, transmission electron microscopy, and field-emission scanning electron microscopy. The electrochemical properties were investigated by cyclic voltammetry, constant current discharge-charge tests, and electrochemical impedance techniques. Applied as an anode in a lithium-ion battery, the material exhibited excellent specific capacities of 130 mAh g-1 (at the rate of 2000 mA g-1) and 96 mAh g-1 (at the rate of 4000 mA g-1) after 100 cycles; the coulombic efficiency was ~99.5 %, indicating excellent rate capability and reversibility. Furthermore, the electrochemical impedance spectra showed improved electrode kinetics after cycling. These results indicate that the porous nanocrystalline TiO2 synthesized by this improved synthesis route might be a promising anode material for high energy and high power density lithium-ion battery applications. © 2012 Springer Science+Business Media New York.